Differential synaptic marker involvement in the different genetic forms of frontotemporal dementia. (31st December 2021) - Esteve, Aitana Sogorb; Nilsson, Johanna; Swift, Imogen J.; Heller, Carolin; Russell, Lucy L.; Peakman, Georgia; Convery, Rhian S.; van Swieten, John C.; Seelaar, Harro; Borroni, Barbara; Galimberti, Daniela; Sanchez‐Valle, Raquel; et al.
Abstract: Background: Approximately a third of frontotemporal dementia (FTD) is genetic with mutations in three genes accounting for the majority of the inheritance: C9orf72, GRN and MAPT . Synaptic dysfunction is a common mechanism in all of them and the use of fluid biomarkers could be helpful to improve the diagnostic accuracy and useful as a readout of cellular dysfunction within therapeutic trials. Method: A total of 193 cerebrospinal fluid samples from the GENetic FTD Initiative including 77 presymptomatic (31 C9orf72, 23 GRN, 23 MAPT ), 55 symptomatic mutation carriers (26 C9orf72, 17 GRN, 12 MAPT ) and 61 mutation‐negative controls were measured using a microflow LC PRM‐MS set‐up targeting 15 synaptic proteins: 14‐3‐3 proteins (eta, zeta/delta and epsilon), AP‐2 complex subunit beta, beta‐synuclein, gamma‐synuclein, complexin‐2, neurogranin, neuronal pentraxin receptor (NPTXR), neuronal pentraxin 1 (NPTX1), neuronal pentraxin 2 (NPTX2), phosphatidylethanolamine‐binding protein 1 (PEBP‐1), rab GDP dissociation inhibitor α (rab GDIα), syntaxin‐1B and syntaxin‐7. Mutation carrier groups were compared to each other and to controls using a bootstrapped linear regression model, adjusting for age and sex. Result: Eight proteins were increased only in symptomatic MAPT mutation carriers (compared with controls) and not in symptomatic C9orf72 or GRN mutation carriers: 14‐3‐3‐eta, beta‐synuclein, gamma‐synuclein, neurogranin, PEBP‐1, rab GDIα, syntaxin‐1B and syntaxin‐7. In contrast, NPTX1 and NPTX2 were affected in all three genetic groups (decreased compared to controls), with NPTXR being affected in C9orf72 and GRN mutation carriers only (decreased compared to controls). No changes were seen in presymptomatic mutation carriers in these proteins. Figure 1 contains p‐values for all significant changes. Conclusion: Differential involvement of synaptic markers is seen in the genetic forms of FTD, with impairment particularly in those with MAPT mutations, with only the neuronal pentraxins affected in GRN and C9orf72 mutation carriers. Further work is needed to explore correlations with clinical and imaging biomarkers, whether there are changes in the late presymptomatic period, and how these markers change over time.